Case Report: Computed tomography-guided diagnosis and surgical removal of intraorbital salivary choristoma confirmed with cytology and histopathology - Morgan, Catharine; Evenhuis, Janny V.; Zurbuchen, Sarah; Vapniarsky, Natalia; Brust, Kelsey (Frontiers in Veterinary Science, 2025)
A 10-year-old male castrated Golden Retriever was presented for evaluation of a 2-year history of a slowly progressing intraorbital mass. Computed tomography showed a large, ovoid, fluid-filled structure that was not clearly associated with the salivary or lacrimal glands. Cytology was most consistent with a mildly inflamed salivary lesion. Surgical removal with biopsy showed that the mass was a cyst-like structure with multifocal serous salivary gland tissue. Histopathologic diagnosis, combined with three-dimensional imaging confirmation of an abnormal anatomic location, is most consistent with salivary choristoma.